The “credit crunch” and the availability of credit to small business - Hancock, Diana; Wilcox, James A (Journal of Banking & Finance, 1998)
We present estimates of how much bank loans and real activity in small businesses responded to changes in banks' capital conditions and other bank and aggregate economic conditions. Using data for 1989–1992 by state, we estimated the effects of those factors on employment, payrolls, and the number of firms by firm size, as well as on gross state product. In response to declines in their own bank capital, small banks shrank their loan portfolios considerably more than large banks did. Large banks tended to increase loans more when small banks were under increased capital pressure than vice versa. Real economic activity was reduced more by capital declines and by loan declines at small banks than at large banks. Small banks were making “high-powered loans” in that dollar-for-dollar loan declines in their loans had larger impacts on economic activity than loan declines at large banks did. Capital declines at small banks produced larger changes in economic activity dollar-for-dollar than capital declines at large banks did. Aggregate economic conditions had smaller effects on small firms than on large firms and smaller effects on small banks than on large banks. The evidence hinted that the volume of loans made under Small Business Administration (SBA) loan guarantee programs shrank less in response to declines in bank capital than the volume of loans not made under the SBA loan guarantee programs.